Rancangan Game Edukasi ”Origin Of Electromagnetism” Menggunakan Unity 2d Berbasis Android Pada Materi Induksi Elektromagnetik - Dylanatha Syahputra (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Physics learning often encounters difficulties in conveying abstract and complex concepts, especially in electromagnetic induction materials. Students tend to struggle in understanding magnetic flux changes and Faraday's law due to limited visualization tools and lack of engaging learning media. This study aims to develop an interactive and engaging educational game as a learning medium on electromagnetic induction material. The game, titled "Origin of Electromagnetism", is designed using Unity 2D and implemented on Android platforms. It combines storytelling elements with virtual experiments based on Oersted's and Faraday's discoveries, presented in a narrative-puzzle format with Pixel art style. This research uses a descriptive method with a development model adapted from the System Development Life Cycle (SDLC) using the Waterfall approach. The development stages include preparation, theoretical study, game planning, expert validation, limited trial, data analysis, and conclusion. Validation was carried out by media experts and users, while student responses were collected through questionnaires.The results show that the average score from media experts reached over 79% (categorized as "Eligible"), while user validation (from physics teachers) reached 89.33% ("Highly Eligible"). Student responses from 21 participants showed an average score above 80%, indicating strong enthusiasm, increased motivation, and improved understanding of the subject matter. In conclusion, the "Origin of Electromagnetism" educational game is a feasible and effective learning medium for physics, particularly in teaching electromagnetic induction concepts. It not only increases students’ interest and engagement but also supports independent and flexible learning through digital platforms.
Reaploud Repository Hasyim April 2026
Keywords: Android Learning Media; Educational Game; Electromagnetic Induction; Interactive Physics; Unity 2D